Product Market Competition and Option Prices - Morellec, Erwan; Zhdanov, Alexei (Review of Financial Studies, 2019)
Most firms face some form of competition in product markets. The degree of competition a firm faces feeds back into its cash flows and affects the values of the securities it issues. Through its effects on stock prices, product market competition affects the prices of options on equity and leads to an inverse relationship between equity returns and volatility, generating a negative volatility skew in option prices. Using a large sample of U.S. equity options, we provide empirical support for this finding and demonstrate the importance of accounting for product market competition when explaining the cross-sectional variation in option skew. Received June 28, 2017; editorial decision October 23, 2018 by Editor Andrew Karolyi. Authors have furnished supplementary Internet Appendices, which is available on the Oxford University Press Web site next to the link to the final published paper online.